Absent pulmonary valve or pulmonary atresia with intact ventricular septum: Which is it?. Issue 11 (4th October 2020) - Nealon, Erin; Berman, Darren; Rowland, Daniel; Boe, Brian; Lloyd, Eric; Cua, Clifford L.
Abstract: A fetal echocardiogram noted valvar pulmonary atresia vs critical pulmonary valve stenosis, confluent pulmonary arteries, patent ductus arteriosus, and an apical muscular ventricular septal defect vs coronary sinusoid. Postnatal echocardiogram documented an absent pulmonary valve, coronary artery fistula to the right ventricle, confluent pulmonary arteries, and a patent ductus arteriosus. Catheterization confirmed the postnatal echocardiographic findings except there was no antegrade flow from the right ventricle to the pulmonary arteries. Close evaluation of all imaging modalities revealed the final diagnosis of absent pulmonary valve with a double‐chambered right ventricle with no egress from the right ventricle to pulmonary artery.